2021
DOI: 10.3390/ijms222212307
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Potential of New Phenolic Hydrazide-Hydrazones with a Decoy Substrate Fragment towards Laccase from a Phytopathogenic Fungus: SAR and Molecular Docking Studies

Abstract: Laccase from pathogenic fungi participates in both the delignification and neutralization of phytoantibiotics. Furthermore, it interferes with the hormone signaling in plants and catalyzes melanization. Infections of these pathogens contribute to loss in forestry, agriculture, and horticulture. As there is still a need to expand knowledge on efficient defense strategies against phytopathogenic fungi, the present study aimed to reveal more information on the molecular mechanisms of laccase inhibition with natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 107 publications
(177 reference statements)
0
29
0
1
Order By: Relevance
“… , Maniak reported that the fungicidal mechanism of phenolic hydrazide-hydrazones derived from coumarin hydrazine was inhibiting laccase (Figure ). Similarly, N -sulfonyl hydrazides based on PMDD-5Y design were also designated as laccase inhibitors by Zhang (Figure ). On the other hand, for the fungicidal acethydrazide compounds reported in the literature, the plasma membrane contraction and separation from the cell wall in the treated fungal cells could be clearly found by TEM observation, while the specific target was unclear (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… , Maniak reported that the fungicidal mechanism of phenolic hydrazide-hydrazones derived from coumarin hydrazine was inhibiting laccase (Figure ). Similarly, N -sulfonyl hydrazides based on PMDD-5Y design were also designated as laccase inhibitors by Zhang (Figure ). On the other hand, for the fungicidal acethydrazide compounds reported in the literature, the plasma membrane contraction and separation from the cell wall in the treated fungal cells could be clearly found by TEM observation, while the specific target was unclear (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Food supply is related to global security and stability, while world grain output has declined due to various superimposed factors in 2022. Therein, phytopathogenic fungi, such as the troublesome filamentous fungi Fusarium graminearum, Rhizoctonia solani, and Pyricularia grisea, seriously affect grain yield and quality. The application of fungicides is the most common method of controlling plant diseases and is essential to improve and secure food production. , In China, Shouguang and Shenxian are the two largest producing cities for facility vegetables. However, with the long-term use of traditional fungicides, the resistance of plant pathogens such as Botrytis cinerea and Colletotrichum gloeosporioides in facility vegetables has become more serious.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrazides are highly bioactive chemicals with broad biological activities, including glycogen phosphorylase inhibitors, insecticides, HIV inhibitors, myeloperoxidase inhibitors, and antituberculous medications (isoniazid) [ 21 ]. Furthermore, hydrazide-hydrazones are commonly utilized as enzyme inhibitors [ 22 ]. Some hydrazones, for example, have been examined as a new class of dual inhibitors of thymidine phosphorylase and cancer cell growth, which merits further investigation for anti-cancer drug development [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…漆酶蛋白结构包含肽链、糖配基、四个铜离子反应 簇, 其晶体结构的解析为漆酶抑制剂的深入研究奠定了 基础 [5] . 当前已报道的漆酶抑制剂主要分为两类: (1)无 机化合物: 金属螯合剂、金属离子、卤素离子等 [6][7][8] ; (2) 有机化合物: 短醇 [9] 、肼腙 [10][11] 、缩氨基硫脲类 [12] 等. 这 些抑制剂可通过螯合铜原子、修饰氨基酸残基、改变糖 蛋白构象或与底物竞争性结合等方式影响漆酶活性.…”
unclassified